Sarcopenia and its determinants among Iranian elderly (SARIR): study protocol - Hashemi, Rezvan (BioMed Central, 2012)
BACKGROUND: The elderly populations increase in world because of improved health status in communities, so health and independency of seniors has become and will be one of the main priorities of public health systems. Ageing have been associated with changes in body composition, including loss of muscle mass, loss of bone mass and increase fat mass. Involuntary age related loss of muscle mass, sarcopenia,has been linked to functional impairment and physical disability. Several definitions for sarcopenia have been presented based on the method of measuring body composition, but an internationally accepted definition doesn’t presently exist yet. In 2010, the European working group on sarcopenia developed a new definition for sarcopenia according to measure muscle mass and muscle function. Several studies have been done about sarcopenia in world, but to our knowledge this study is the first in Iran which is one of the largest countries of the Middle East that faces a fast growing elderly population. The aim of this study is to evaluate sarcopenia and related risk factors in Iran according new definition of sarcopenia. METHODS: This study will be conducted in two phase among elderly men and women over 55 years in the 6(th) district of TehranThe first phase will be a population-based cross-sectional study to determine the frequency of sarcopenia in the study population, and to conduct case finding for the second phase. The second phase will be a case–control study to comparison the metabolic and inflammatory factors in sarcopenic and non sarcopenic groups. The association between sarcopenia and major dietary pattern will be evaluated using factor analysis. CONCLUSION: This study is the first study that evaluates sarcopenia and its risk factor in Iranian elderlies. We discuss details of how we collect the data and appropriate instruments to measure muscle mass, muscle power and muscle strength, and suitable cut- off to define sarcopenia in Iranian elderlies. We believe the result of our study can be useful to health policy makers prepare the necessary infrastructure for elderly health improvements and increase the quality of life in geriatric.